2022
DOI: 10.3389/fmed.2022.793615
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of Biofilm Formation and Antibiotic Resistance in Acinetobacter baumannii Infection

Abstract: Acinetobacter baumannii (A. baumannii) is a leading cause of nosocomial infections as this pathogen has certain attributes that facilitate the subversion of natural defenses of the human body. A. baumannii acquires antibiotic resistance determinants easily and can thrive on both biotic and abiotic surfaces. Different resistance mechanisms or determinants, both transmissible and non-transmissible, have aided in this victory over antibiotics. In addition, the propensity to form biofilms (communities of organism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 340 publications
(356 reference statements)
0
43
0
1
Order By: Relevance
“…Acinetobacter baumannii is an important opportunistic pathogen that causes a variety of infections in hospital settings, particularly in critically ill patients with predisposing risk factors such as an intensive care unit stay, assisted ventilation, surgical interventions, invasive procedures, and the presence of indwelling devices (catheters, drainage or endotracheal tubes, and artificial implants) [ 1 , 2 ]. Factors that contribute to an increasing trend of A. baumannii nosocomial infections worldwide sum up its persistence and growth in medical wards due to resistance to desiccation, disinfectants, and antibiotics, and ability to form biofilm on biotic and abiotic surfaces [ 1 ]. Until recently, carbapenems were the standard therapy for treating A. baumannii nosocomial infections.…”
Section: Introductionmentioning
confidence: 99%
“…Acinetobacter baumannii is an important opportunistic pathogen that causes a variety of infections in hospital settings, particularly in critically ill patients with predisposing risk factors such as an intensive care unit stay, assisted ventilation, surgical interventions, invasive procedures, and the presence of indwelling devices (catheters, drainage or endotracheal tubes, and artificial implants) [ 1 , 2 ]. Factors that contribute to an increasing trend of A. baumannii nosocomial infections worldwide sum up its persistence and growth in medical wards due to resistance to desiccation, disinfectants, and antibiotics, and ability to form biofilm on biotic and abiotic surfaces [ 1 ]. Until recently, carbapenems were the standard therapy for treating A. baumannii nosocomial infections.…”
Section: Introductionmentioning
confidence: 99%
“…Bronchoscopy is one of the standard methods to diagnose respiratory diseases. Studies have shown that A. baumannii and K. pneumoniae readily colonizes the surfaces of medical devices, especially tracheal tubes, by forming biofilms ( Chung, 2016 ; Roy et al., 2022 ). Bringing colonized bacteria into the lesion during the examination and subsequently causing infection ( Sato et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm formation and maintenance have also been associated with intracellular communication, mediated by 3′,5′-cyclic diguanylic acid and quorum sensing, which is facilitated by AtaI autoinducer synthase and the AbaR cognate receptor [ 50 ] ( Figure 1 ). Additionally, the association or correlation between biofilm formation and antibiotic resistance has been extensively investigated [ 54 , 55 , 56 ]. For example, Thummeepak et al [ 54 ] investigated the association between biofilm formation, antibiotic resistance phenotype, and virulence genes in clinical A. baumannii ( n = 225) isolates, with 86.2% of the strains characterised as MDR, of which 76.9% were biofilm producers.…”
Section: Acinetobacter Baumannii Virulome—virulence Factors ...mentioning
confidence: 99%